P-261 Assessing the impact of interventions to promote clinical effectiveness in a palliative care service. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Loveday, Nicola; Curtis, Matthew
Abstract : Background: Clinical effectiveness is a major component of clinical governance and integral to the successful operation of a palliative care service (PCS). Our PCS delivers regular internal educational programmes to share recent developments and latest knowledge and thereby promote high standards of care. Educational theory would suggest that different approaches might suit particular staff groups but it is not clear which approaches are best. Aims: To assess the most effective method to disseminate new learning throughout the PCS. To explore whether professional group is relevant to structure of learning event. Method: Delivery of the same material (highly relevant published paper, pertinent to specialists' practice) using two different approaches. Session 1: CNS group. Paper distributed to all participants; read before the teaching session. Each allocated a section; presented findings at small group session. Researchers (two doctors) present to facilitate discussion. Session 2: Doctors of all grades; researchers (same two doctors) presented the paper, reflecting on pertinent points. Structured questions throughout; highly interactive session. Identical short survey sent before and after intervention to compare clinicians' baseline and post-teaching knowledge; a proxy measure of the effectiveness of said intervention. Results: Both groups had improved knowledge post-intervention. Baseline knowledge of CNSs was better than doctors (53% v. 40% correct). CNSs demonstrated better post-teaching knowledge than doctors (95% v. 78%). Conclusion: This work highlights the importance of evaluating the impact of interventions to promote clinical effectiveness and seems to show that one form of intervention may be superior to the other. Future work should now focus on whether this 'more effective' approach is effective for doctors. Due to small numbers of learners, the team plan to continually assess these approaches over a number of topics. Further study to see whether this learning has a positive impact on practice and the outcomes for patients.